Overfertilization reduces tomato yield under long-term continuous cropping system via regulation of soil microbial community composition - Song, Qiaobo; Fu, Hongdan; Shi, Qingwen; Shan, Xuan; Wang, Zhen; Sun, Zhouping; Li, Tianlai (Frontiers in Microbiology, 2022)
Long-term monoculture cropping and over-fertilization degrade soil fertility, which declines the crop and promotes the development of soil borne diseases. However, it remains unclear what are the temporal effects of named above factors on the chemical properties and microbial community structure. Thus, a greenhouse experiment with various amount fertilization (2196 kg ha-1 (control) and 6588 kg ha-1 (over-fertilization) of inorganic fertilizers (NPK)) was carried out with the soils used previously 1, 2, and 12-y under monoculture of tomato. Fertilization rather than cropping duration had greater impact on tomato yield. A decrease of yield by 0.24 times was caused by over-fertilization in 12-y soils. 12-y over-fertilization decreased pH in 1.37 units. Bacterial diversity and richness decreased 0.06 and 0.31 times under over-fertilization in 12-y soil, compared to the control. Relative abundance of Gemmatimonas and Gp6 in 12-y soil was 0.21 and 3.62 times lower than in control soil under over-fertilization. Bacterial and fungal community composition rather than diversity were main driver to regulate the yield. Thus, over-fertilization suppressed tomato yield by inhibiting the relative abundance of beneficial microorganisms.